Multivariate Morphometric Confirmation of Solidago chilensis (Asteraceae: Astereae) in Azores - Semple, John C. (2017)
An herbarium collection of Solidago from near Pico Island, Azores, Portugal, is reported here tobe Solidago chilensis Meyen. One collection (Botelho Gonçalves 1825, BM) was included in amultivariate morphometric analysis comparing S. altissima, S. canadensis, S. chilensis, and S. gigantea.The specimen has glabrous lower and mid stems, glabrous linear lanceolate upper stem leaves with ciliateentire margins, and secund pyramidal inflorescences that are much longer than wide.